Development of Prophetic Education Curriculum Management in student boarding schools (Lembaran Ilmu Kependidikan, 2023)
The issue of developing prophetic education curriculum management in student boarding schools is the lack of student involvement in developing a prophetic education curriculum. The purpose of this study is to find and describe the development of curriculum management and character education methods implemented in Pesma An-Najah Purwokerto. The results of the research are first, curriculum development is carried out by formulating a substantial curriculum plan whose main content is prophetic knowledge and values, organizing curriculum to organize various activities and learning materials of prophetic education; implementing the prophetic education curriculum in daily learning activities; and supervision of the implementation of the prophetic education curriculum carried out by deliberation for the needs of men. Evaluate and determine the following policy. Second, the development of prophetic education methods is carried out by the hiwar (conversation) method of the Qurani and Nabawi, the method of Quranic and Prophetic stories, the method of amtsal (parables), the method of uswah (example), the method of taking ibrah (lesson) and mau'izhah (warning), and the method of targhib (making pleasure) and tarhib (scares). With the development of this curriculum and method, the practice of learning and teaching at Pondok An-Najah is carried out with the content of prophetic education materials can be done smoothly, good, and sustainably